1991
DOI: 10.1002/hep.1840140637
|View full text |Cite
|
Sign up to set email alerts
|

Iron and uroporphyrin in hepatocytes of inbred mice in experimental porphyria: A biochemical and morphological study

Abstract: In C57BL/10 mice, experimental porphyria can be induced by iron overload alone; uroporphyrin crystals and ferritin iron are located in the same hepatocyte; and the morphological co-occurrence of uroporphyrin crystals and ferritin iron in hepatocytes suggests a role for iron (as ferritin) in the pathogenesis of porphyria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…[30][31][32] In contrast, in Fe dextran-treated wild-type mice, Fe is found in both parenchymal and Kupffer cells, with massive loading in Kupffer cells. 23,41 Previously, it was shown that in ALAtreated SWR mice, large doses of Fe dextran (500 mg Fe/kg) are required to maximize URO accumulation. 24 Perhaps these high doses were needed to produce sufficient Fe accumulation in the parenchymal cells to induce uroporphyria in this mouse strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] In contrast, in Fe dextran-treated wild-type mice, Fe is found in both parenchymal and Kupffer cells, with massive loading in Kupffer cells. 23,41 Previously, it was shown that in ALAtreated SWR mice, large doses of Fe dextran (500 mg Fe/kg) are required to maximize URO accumulation. 24 Perhaps these high doses were needed to produce sufficient Fe accumulation in the parenchymal cells to induce uroporphyria in this mouse strain.…”
Section: Discussionmentioning
confidence: 99%
“…20,43 In addition, no ALA treatment is necessary to cause development of uroporphyria in some mouse strains given Fe dextran alone. 24,41 However, Bechara et al have postulated that metals catalyze the formation of an ALA radical 44 that can release Fe from ferritin in vitro. 45 This group also reported some increases in hepatic non-heme Fe in rats acutely treated with parenteral ALA, 45 or with an inhibitor of ALA dehydrase.…”
Section: Discussionmentioning
confidence: 99%